Symposium 2: Network theories for technology-enabled learning and social change: Connectivism and Actor Network theory - Bell, Frances (Proceedings of the International Conference on Networked Learning, 2010)
Learning never was confined to classrooms. We all learn in, out of, before, during and after episodes of formal education. The changing sociotechnical context offers a promise of new opportunities, and the sense that somehow things may be different. Use of the Internet and other emerging technologies is spreading in frequency, time and space. People and organizations wish to use technology to support learning seek theories to frame their understanding and their innovations. In this article we explore Connectivism, that is positioned as a theory for the digital age, in use on a Massive Open Online Course (MOOC), Connectivism and Connective Knowledge, in 2008. We then compare Connectivism with another network theory, Actor Network Theory, to explore possible synergies. We found that Connectivism enables educators and learners to legitimise their use of technology to support teaching and learning. Connectivism, a relatively new theory, can benefit from a richer empirical base as it develops. Since the scope of educational change can vary from a specific learning setting through organisational and societal settings, we can develop theories through empirical exploration of cases across the range of settings to support our understanding and actions.